Impact of financial management centralisation in a health system under austerity: a qualitative study from South Africa - Jane Goudge; Jodi Wishnia (BMJ Global Health)
Introduction International calls for universal health coverage (UHC) have led many countries to implement health sector reforms, however, since the 2008 global recession, economic growth has slowed in many lower-income and middle-income countries. In a renewed interest in public financial management (PFM), international organisations have emphasised the importance of giving spending control to those responsible for healthcare. However, centralisation is a common response when there is a need to cut expenditure due to a reduced budget; yet failure to decentralise often hampers the achievement of important goals. This paper examines the effect of centralising financial decision-making on the functioning of the South African health system.Methods We used a case study design with an ethnographic approach. Primary data collection was conducted through participant-observation and semistructured interviews, over 1 year. Member checking was conducted.Results New management implemented centralisation due to a reduced budget, a history of financial mismanagement, the punitive regulatory environment financial managers face, and their fear of poor audit outcomes. The reform, together with an authoritarian management style to ensure compliance, created a large power distance between financial and clinical managers. District managers felt that there was poor communication about the reform and that decision-making was opaque. This lowered commitment to the reform, even for those who thought it was necessary. It also reduced communal action, creating an individualistic environment. The authoritarian management style, and the impact of centralisation on service delivery, negatively affected planning and decision making, impairing organisational functioning.Conclusion As public health systems become even more financially constrained, recognising how PFM reforms can influence organisational culture, and how the negative effects can be mitigated, is of international importance. We highlight the importance of a participatory culture that encourages shared decision making and coproduction, particularly as countries grapple with how to achieve UHC with limited funds.